Petrologia magnética dos granodioritos Água Azul e Água Limpa, porção sul do Domínio Carajás - Pará - GABRIEL, Eleilson Oliveira (2015)
The Água Azul and Água Limpa granodiorites (AAGrd and ALGrd, respectively) outcrop in the extreme southern of the Carajás Domain as two elongated bodies following the EW regional trend and were previously included in the Xingu Complex. The ALGrd consists mainly of biotite-amphibole granodiorites and muscovite-biotite granodiorites, with subordinate amphibole-biotite tonalites; the AAGrd contains dominant epidote-amphibole-biotite granodiorites, epidote-amphibole-biotite tonalite and restricted (amphibole)-epidote-biotite monzogranites. These rocks show geochemical signatures like of archaean sanukitoids. The magnetic susceptibility (MS) values obtained in the ALGrd (average 17.54 × 10-4 SIv) and AAGrd (average 4.19 × 10-4 SIv) are relatively low. The main opaque minerals are magnetite and hematite, and ilmenite is lacking in these rocks. The ALGrd contains titanite associated with magnetite, while the AAGrd contains pyrite, chalcopyrite, and goethite. In the ALGrd, magnetite is more developed and large than in the AAGrd, justifying its highest values of MS. The oxidation of magnetite (martitization) and the alteration of sulfides to goethite, occurred at low temperatures. The positive correlation between MS values and the modal content of opaque, amphibole, epidote + allanite and quartz + K-feldspar, as well as the negative correlation of MS with biotite and mafic observed in these units, reveal a trend of MS increasing in the direction: amphibole tonalites/amphibole granodiorites à biotite granodiorites/biotite monzogranites. The geochemical data confirm this fact, with a negative correlation between the MS values and Fe2O3T, FeO, and MgO, reflecting, for the two units, an upward trend in MS values parallel to magmatic differentiation. The geochemical and mineralogical affinities between these rocks and sanukitoids of the Rio Maria Domain suggest conditions of the oxygen fugacity between HM and FMQ buffers for the studied granitoids.